Disruptions as opportunities for new thinking: applying the studio model to business education. Issue 1 (2nd January 2020) - Bandera, Cesar; Somers, Mark; Passerini, Katia; Naatus, Mary Kate; Pon, Kevin
ABSTRACT: This paper proposes that to overcome the threat of disruption brought about by a new education model that is flexible, personalised and low cost, universities should focus on adding value not to their replicable content, but to the collaboration and socialisation processes that localise learning to the context where learning occurs whether it be inside or outside the classroom. The studio model, commonly found in arts and architecture, is a suitable example of this localisation approach in that it offers an opportunity to innovate through continuous collaboration. Design thinking approaches in education represent a pathway to achieving the creative results sought by the studio model, and this paper outlines a conceptual and practical model of how this can be done in the field of management and business education.